ON THE POTENTIAL OF THE EDUCATIONAL PROCESS IN CONDUCTING LEGAL AND LINGUISTIC MONITORING OF CURRENT LEGISLATION (On the example of the code of the Republic of Kazakhstan «Оn marriage (matrimony) and family») (VERITAS LEGIS JOURNAL, 2026)
The issue of the quality of the text of the current legislation of the Republic of Kazakhstan in the Kazakh language is a natural phenomenon and, along with society and the media, is constantly in the focus of attention of the scientific community conducting various studies in the field of law and linguistics. Obviously, the issue of the quality of legislation in the Kazakh language, which remains translatable for various objective and subjective reasons, will not be off the agenda in the near future.   A lot has been written about the linguistic and legal errors that exist in the normative legal acts adopted in different periods and years of State Independence. The society also shows great interest in correcting this situation. Nevertheless, everyone knows that it does not yet enjoy the support of the authorized structures of the state. Along with such areas as language policy, political will, support for the state language, the development of qualitative norms, and the establishment of justice, there are factors such as the weakness of the theoretical and philological foundations of rulemaking in the Kazakh language, and the shortage of specialists who are equally proficient in law and linguistics. Therefore, legal and linguistic monitoring should also be included among the measures of a political, legal, socio-economic and other nature to improve the quality of the text of the current legislation in the Kazakh language.  In this regard, the purpose of this work is to consider the possibility of using the enormous potential of legal and linguistic monitoring in the educational process in correcting errors in current legislation. To achieve this goal, the article examines the problems of studying, identifying together with students and including on the agenda the issue of correcting the errors of the current legislation.
Keywords: educational process; law; legislation; legal monitoring; legal and linguistic monitoring; vocabulary